Iron Oxide Nanoparticles: Enhanced Collective Magnetic Properties Induced by the Controlled Assembly of Iron Oxide Nanoparticles in Chains (Adv. Funct. Mater. 15/2016). (April 2016) - Toulemon, Delphine; Rastei, Mircea V.; Schmool, David; Garitaonandia, José Sáiz; Lezama, Luis; Cattoën, Xavier; Bégin‐Colin, Sylvie; Pichon, Benoit P.
Abstract : Highly anisotropic assemblies of magnetic nanoparticles featuring enhanced collective properties are gaining interest for spintronic and biomedical applications. On page 2454, B. P. Pichon and co‐workers report a very efficient and robust approach based on "click" chemistry performed under a magnetic field to produce co‐linear single nanoparticle chains with well‐defined separating distances controlling intra‐ vs. inter‐chain magnetic coupling. The authors would like to thank Agnieszka Koziol for the preparation of the cover design.